2008
DOI: 10.1161/hypertensionaha.107.097154
|View full text |Cite
|
Sign up to set email alerts
|

Role of Carbon Monoxide in Blood Pressure Regulation

Abstract: C arbon monoxide (CO) is an odorless, colorless, tasteless gas that is generated in the environment as the result of combustion from stoves and engines among other sources. Approximately 500 people per year in the United States are victims of nonfire-associated CO poisoning according to the Centers for Disease Control and Prevention. CO poisoning is often fatal because of its interaction with hemoglobin, which renders it incapable of carrying oxygen-causing organs to become severely hypoxic. CO inhalation is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 98 publications
0
25
0
1
Order By: Relevance
“…The activation of K þ channels leads to membrane hyperpolarization, which in turn inhibits voltage-gated Ca 2þ channels, causing SMC relaxation (276). HO-derived CO may facilitate the vasodilatory action of NO by stimulating cGMP levels in VSMCs (84,244) (Fig. 13A).…”
Section: B Effect Of Ho-1=co Pathway On Vascular Homeostasismentioning
confidence: 99%
“…The activation of K þ channels leads to membrane hyperpolarization, which in turn inhibits voltage-gated Ca 2þ channels, causing SMC relaxation (276). HO-derived CO may facilitate the vasodilatory action of NO by stimulating cGMP levels in VSMCs (84,244) (Fig. 13A).…”
Section: B Effect Of Ho-1=co Pathway On Vascular Homeostasismentioning
confidence: 99%
“…Carbon monoxide (CO) possesses anti-inflammatory, antiapoptotic, and antioxidant activities, suggesting that it could be used to prevent organ damage caused by ischemia-reperfusion injury (Otterbein et al, 2000;Brouard et al, 2002;Zuckerbraun et al, 2005;Stec et al, 2008;Motterlini and Otterbein, 2010). Nakao et al, 2008 recently reported an interesting observation, in which the exposure of organ preservation solutions to CO was effective in suppressing the postreperfusion reduction in renal P450 levels in a rat model of kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] CO is predominantly released during heme metabolism by heme oxygenase (HO), generating iron and biliverdin. Biliverdin is further metabolized to bilirubin by biliverdin reductase.…”
mentioning
confidence: 99%